Prognostic importance of brain natriuretic peptide and left ventricular longitudinal function in asymptomatic degenerative mitral regurgitation. Issue 7 (18th February 2012) - Magne, Julien; Mahjoub, Haifa; Pierard, Luc A; O'Connor, Kim; Pirlet, Charles; Pibarot, Philippe; Lancellotti, Patrizio
Abstract : Objectives: To identify the determinants and the impact on outcome of brain natriuretic peptide (BNP) in asymptomatic patients with degenerative mitral regurgitation (MR). Method: Comprehensive transthoracic echocardiography including two-dimensional speckle tracking quantification was performed in 135 consecutive asymptomatic patients (60±14 years, 56% men) with moderate to severe degenerative MR and preserved left ventricular (LV) function. Blood samples were collected at the time of the echocardiography and plasma BNP levels were measured. Main outcome measures: BNP level and cardiac events. Results: BNP was correlated with age, indexed LV end-systolic diameter, indexed left atrium (LA) volume, estimated LV filling pressure with E/Ea ratio, systolic pulmonary arterial pressure and global longitudinal strain (GLS). In multiple regression analysis, indexed LA volume (p=0.008), mitral deceleration time (p=0.003) and GLS (p<0.0001) were independently associated with BNP. During follow-up (mean=23±19 months), 54 events occurred resulting in 4-year event-free survival of 50±6%. There was a graded relationship between the increase in BNP (ie, according to quartile) and reduced event-free survival (p<0.0001). In Cox multivariable analysis, indexed LA volume (HR=1.04, p=0.003), GLS (HR=1.14, p=0.007) and 3rd and 4th quartiles of BNP (HR=8.5, p=0.002 and HR=8.8, p=0.002) were independent determinants of event-free survival. Conclusion: In asymptomatic degenerative MR, LV longitudinal function and LA volume are the main determinants of BNP release. BNP is a powerful independent predictor of cardiac events. Measurement of plasma BNP may help to improve risk stratification and management of asymptomatic patients with degenerative MR.